An investigation into novel components and signalling mechanisms of inflammasomes - Becker, Christine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2010)
This thesis concerns an analysis of caspase-1 and ASC, key components of the inflammasome. At the outset Rab39a had been found in a complex with caspase-1. Rab39a is a member of the Rab GTPase family, a group of proteins which have important roles in protein trafficking and secretion. Rab39a was successfully cloned and its binding to caspase-1 was confirmed by co-immunoprecipitation and confocal microscopy experiments. Biological assays were carried out to try and determine the ftinctional relevance of this interaction. Bioinformatic analysis showed that Rab39a contains a highly conserved caspase-1 cleavage site and can be cleaved in the presence of recombinant caspase-1 or in cells treated with LPS and ATP. Rab39a was found to localise with active caspases on phagosomes formed in response to S. aureus and was shown to have a role in bacterial uptake. The Rab39a promoter contains many putative transcription factor binding sites and Real Time PCR analysis showed that Rab39a mRNA levels are significantly increased in response to LPS, Malp2 and Pam3Cys.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin